The City's Celebration and the City of Celebration - Salmin, Leonid (project baikal, 2020)
The article considers relations and mutual influence of a celebration as a ritual and a city as a space where a celebration develops and transforms throughout many centuries. The article analyses the features of pre-urban genesis of celebrations in the context of the city, a medieval model of the urban celebration and a semantic hollowing-out of the celebration in the modern and contemporary times.
Keywords: celebration in a city; medieval city; localisation; people's body; celebration choreography; piazza; mythology; ritual